Efficacy of Postbiotics in a PRP-Like Cosmetic Product for the Treatment of Alopecia Area Celsi: A Randomized Double-Blinded Parallel-Group Study - Fabio Rinaldi; Anna Trink; Daniela Pinto (Adis, Springer Healthcare, 2020)
Abstract Introduction Alopecia areata (AA), also known as 'area Celsi', is the second most common form of hair loss affecting the scalp. Newly proposed treatments for AA include low-level light therapy, biologics such as Janus kinase inhibitors and autologous platelet-rich plasma (PRP), which is a well-known "elixir" for hair growth. Bioactive peptides developed through biotechnological applications have been used to overcome the limitations of PRP. More recently, the involvement of microbiota in hair growth disorders, in AA in particular, has been reported, and the usefulness of microbial metabolites, i.e. postbiotics, has been suggested. Methods This study was a randomized double-blinded parallel-group study in which 160 persons of both sexes affected by AA and aged between 18 and 60 years were enrolled. The subjects were randomly assigned to a treatment group (group 1), receiving the TR-PRP plus-Celsi cosmetic product, and a placebo group (group 2). The SALT (Severity of Alopecia Tool) score was determined in both groups at baseline and after 2 and 3 months of treatment, and the results compared between groups. Results The subjects in group 1 showed a significant change from baseline in SALT score at 2 months of treatment (61.04% ± 3.45%; p < 0.0001), with a further improvement at the end of treatment (3 months) (69.56% ± 4.32%; p < 0.0001). No significant changes from baseline were reported for the subjects in group 2 (T1: 26.45% ± 3.64%; T3: 27.63% ± 7.61%). Conclusions The results of this study provide further proof of the efficacy of bioactive peptides that mimick the growth factors present in PRP in subjects affected by AA. They also add to our knowledge of the link between microbiota and hair growth disorders, emphasizing the importance of studies on the microbial community and microbial metabolites as a novel therapeutic approach.